Fishing culture in decline - Mumbai Archive Project Team (Jio Institute, 2024)
In present-day Kandivli village, fishing activities are notably absent despite a sizeable Koli community residing there. Yashwant Keni, though no longer a fisherman, was actively engaged in the fishing business during his younger years. He sourced fish from the Borivali fish market and sold them in Kandivli village to make a living.